The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1934578x211057694
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Piper nigrum and Piperine on Growth, Migration, and Invasion of PANC-1 Human Pancreatic Cancer Cells

Abstract: Several dietary and medicinal herbs have been shown to be effective in the treatment and prevention of cancer. Although Piper nigrum has been shown to have anti-cancer activities against various cancer cells, its anti-pancreatic cancer properties have not been reported. In the present study, P. nigrum extract (PNE) inhibited proliferation of PANC-1 human pancreatic cancer cells. Flow cytometry showed G0/G1 arrest caused by PNE in PANC-1 cells. In addition, Western blot analysis showed that PNE suppressed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Rajarajan et al reported that the dietary piperine represented a potential candidate that could suppress obesity-associated breast cancer growth and metastasis by regulating the miR-181c-3p/PPARα Axis [ 33 ]. Furthermore, Jeong et al also found that piperine has anticancer properties such as growth inhibition, anti-migration, and anti-invasion of cancer cells [ 34 ]. In order to application of piperine derivatives as more potential anticancer drugs, structural modification has received much attention.…”
Section: Bioactivities Of Piperine and Its Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…Rajarajan et al reported that the dietary piperine represented a potential candidate that could suppress obesity-associated breast cancer growth and metastasis by regulating the miR-181c-3p/PPARα Axis [ 33 ]. Furthermore, Jeong et al also found that piperine has anticancer properties such as growth inhibition, anti-migration, and anti-invasion of cancer cells [ 34 ]. In order to application of piperine derivatives as more potential anticancer drugs, structural modification has received much attention.…”
Section: Bioactivities Of Piperine and Its Derivativesmentioning
confidence: 99%
“…Molecular modeling revealed several interactions between derivates and acetylcholinesterase (AChE) substrate binding sites responsible for binding and inhibition [ 65 ]. As shown in Scheme 9 , twenty-two piperine derivates 2 , 52a – 52l , and 53a – 53i were synthesized by Zhong et al and evaluated for their anticancer properties [ 34 ]. As shown in Scheme 10 , a series of novel piperine derivates 56a – 56z , 56a’ – 56b’ , and 59a – 59b containing a linear bisamide were synthesized and evaluated for their insecticidal activities against P. xylostella [ 50 ].…”
Section: Structural Modifications Of Piperine and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Piperine is also known to be able to inhibit the quorum sensing system in the bacterium Chromobacterium violaceum CV026 with an effective dose of 30 mg/L so that it has potential as an antibacterial [31]. Piperine exhibits anti-proliferative, anti-migratory, and anti-invasive properties in human pancreatic cancer cells, PANC-1 [39]. Piperine has a hepatoprotective effect against Dgalactosamine (D-GalN)/lipopolysaccharideinduced damage to rat primary hepatocyte cells (LPS) [17].…”
Section: Piperinementioning
confidence: 99%